Color for architects - Serra Lluch, Juan (Princeton Architectural Press, 2019)
Color for Architects is a clear, concise primer for designers of every kind. This richly illustrated volume provides in-depth and engaging guidance on three major topics: Color Basics covers fundamentals of color perception and theory, systems of color notation, and criteria for harmonious color combinations. Color for the Architectural Project addresses issues architects face in everyday practice, examining history and aesthetics, visual ergonomics, psychology, color-trend forecasting and branding, and the use of color in architectural proposals. Color in the Workflow explains best practices for viewing and communicating color accurately, calibrating equipment, evaluating and managing color in contruction, and creating and editing photographs pf completed work. Throughout, built examples, exercises, and activities allow students and practitioners to apply their study of color to real-world situations. Color for Architects is an indispensable handbook of this essential component of design.
Keywords: Ästhetik; Farbenlehre; Architektur